Effects of Root Debridement With Hand Curettes and Er:YAG Laser on Chemical Properties and Ultrastructure of Periodontally-Diseased Root Surfaces Using Spectroscopy and Scanning Electron Microscopy - Amid, Reza; Gholami, Gholamali; Mojahedi, Masoud; Aghalou, Maryam; Gholami, Mohsen; Mirakhori, Mahdieh (Journal of Lasers in Medical Sciences, 2017)
Introduction: The efficacy of erbium-doped yttrium aluminum garnet (Er:YAG) laser for root debridement in comparison with curettes has been the subject of many recent investigations. Considering the possibility of chemical and ultra-structural changes in root surfaces following laser irradiation, this study sought to assess the effects of scaling and root planing (SRP) with curettes and Er:YAG laser on chemical properties and ultrastructure of root surfaces using spectroscopy and scanning electron microscopy (SEM). Methods: In this in vitro experimental study, extracted sound human single-rooted teeth (n = 50) were randomly scaled using manual curettes alone or in conjunction with Er:YAG laser at 100 and 150 mJ/pulse output energies. The weight percentages of carbon, oxygen, phosphorous and calcium remaining on the root surfaces were calculated using spectroscopy and the surface morphology of specimens was assessed under SEM. Data were analyzed using one-way analysis of variance (ANOVA). Results: No significant differences (P > 0.05) were noted in the mean carbon, oxygen, phosphorous and calcium weight percentages on root surfaces following SRP using manual curettes with and without laser irradiation at both output energies. Laser irradiation after SRP with curettes yielded rougher surfaces compared to the use of curettes alone. Conclusion: Although laser irradiation yielded rougher surfaces, root surfaces were not significantly different in terms of chemical composition following SRP using manual curettes with and without Er:YAG laser irradiation. Er:YAG laser can be safely used as an adjunct to curettes for SRP.